Menjembatani Tuntutan dan Imbalan: Peran Motivasi Kerja pada Kinerja Pegawai Kantor Pemerintah - Jihan Dhinar Pradeta Sari; Wisnu Mahendri (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Employee performance in public service institutions plays a strategic role in determining the quality of services delivered to the community. In the context of the PPKB PPPA Office of Jombang Regency, employee performance is influenced by dynamic workloads and relatively fixed compensation structures. While workload and compensation are often regarded as direct determinants of performance, previous research has produced inconsistent findings, indicating the need to incorporate psychological variables. Work motivation is positioned as a mediating factor in this relationship. A quantitative approach was employed involving 55 non-civil servant staff and family planning field officers, who completed a Likert-scale questionnaire. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) through SmartPLS 4. The findings reveal that workload has a significant positive effect on work motivation, whereas compensation shows no meaningful influence. Work motivation emerges as the only variable with a direct and significant effect on employee performance. Furthermore, work motivation fully mediates the relationship between workload and performance, but does not mediate the relationship between compensation and performance. These results indicate that employee performance within the institution is driven more by intrinsic motivation rooted in responsibility and professional commitment than by financial rewards. Practical implications highlight the need for sustainable non-financial motivation strategies, including recognition systems, opportunities for competency development, and supportive collaborative work environments.